The implementation of the child-friendly school program in fostering students’ morality - Fany Oktavia; Iim Wasliman (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to describe the moral condition of students, analyze the implementation of the Child-Friendly School Program (SRA) in moral development, identify supporting and inhibiting factors for its implementation, and formulate relevant implementation strategies for moral development at the high school level. The research approach used is qualitative with a case study method, which involves two schools, namely SMAN 1 Soreang and SMAN 22 Bandung. Data were collected through interviews, observations, and documentation studies, then analyzed by reduction, presentation, and conclusion drawing techniques.The results of the study show that the implementation of SRA in both schools plays an important role in strengthening student morale through collaboration between schools, parents, and the community. SMAN 1 Soreang stands out in its structured planning and supervision system, while SMAN 22 Bandung emphasizes religious habituation and school community participation. These differences in approaches suggest that the effectiveness of SRA is contextual and influenced by school culture. The study also affirms that successful moral development requires comprehensive planning, participatory organizing, value-based implementation, and ongoing dialogical evaluation. The novelty of this research lies in the integration of moral values in the implementation of SRA through an educational management approach that is adaptive to socio-cultural contexts and digital ethical challenges. These findings are expected to strengthen the implementation of national policies to strengthen character education and Pancasila Student Profiles through the development of a sustainable and contextual SRA model.